The prevalence of haemochromatosis gene mutations in the West of Scotland and their relation to ischaemic heart disease. Issue 9 (15th August 2003) - Campbell, S; George, D K; Robb, S D; Spooner, R; McDonagh, T A; Dargie, H J; Mills, P R
Abstract : Objectives: Excess iron stores have been postulated to enhance the risk of ischaemic heart disease. This study aims to determine whether the two major mutations of the haemochromatosis (HFE) gene (C282Y and H63D) are associated with ischaemic heart disease (IHD) or myocardial infarction (MI). Design: Cross sectional case–control study. Setting: The geographical area studied by the MONICA (monitoring trends and determinants in cardiovascular disease) heart attack register for North Glasgow in Scotland, UK. Patients: 1009 control subjects chosen at random from general practitioner registers were studied. Additionally, 924 subjects who had survived a first MI sustained between 1985 and 1992 were identified from the MONICA register. Main outcome measures: C282Y and H63D mutations, previous MI, and presence or absence of IHD. Results: Mutant gene prevalences in the whole control population were as follows: C282Y: homozygote 0.9%, heterozygote 17.7%; H63D: homozygote 2.1%, heterozygote 25.5%; and compound heterozygote: 2.4%. Analysis by χ 2 test and logistic regression analysis did not identify any significant difference in genotype prevalence between normal control, IHD control, and MI survivor groups. Conclusions: The C282Y homozygote and heterozygote prevalences are among the highest reported worldwide. No association between IHD or MI and HFE genotype was identified. However, these results need to be interpreted in the light of the cross sectional case–control nature of the study.